The Cheese Pairing Cookbook - Morgan McGlynn Carr (The Complete Cheese Pairing Cookbook, 2024)
Morgan McGlynn Carr’s The Complete Cheese Pairing Cookbook is the definitive guide to pairing cheeses with complementary foods and drinks, aimed at cheese lovers of all skill levels—from beginners to aficionados